ETHICAL IMPLICATION OF GOD CONCEPT IN JAVANESE PRAYERS - Sartini Sartini (Jurnal Masyarakat dan Budaya, 2021)
This research is based on the lack of understanding of the meaning of a ritual and prayer which often causes conflict in society. Accusations of infidelity against someone are often used as an excuse for disliking and even attacking groups of accused. Java, which is full of rituals and variations in prayer, is one of the objects of indecency and friction in society. This research reveals the existence of God's role in Javanese prayer. The study was conducted by exploring the meaning of prayer, the types of Javanese prayer, the concept of God in Javanese prayer, and the ethical implications of prayer. This research is a library research regarding the concepts that exist in society. In order to obtain the research results, reading sources were collected, reference reading, description, classification, analysis and conclusion. The results of this study shows that prayer is a greeting or an expression of desire in the form of a statement of the existence of God or a supernatural entity, worship, request, submission, gratitude and an expression of gratitude. Javanese prayer is divided into two, namely the Slametan prayer and mantra. Most Javanese prayers, especially the Slametan prayers and mantra prayers that are good in nature, contain elements of the name of God, while others contain elements of the Prophet, companions of the Prophet, religious propagators, and ancestors. This means belief in God's power and respect for those who play a role in life. Prayers that tend to be negative in nature indicate that they do not mention the name of God and respected life figures. Slametan prayer is positive and communal, contains ethics, and also hopes for the good of the prayer person and all humans.